A general solution to the output-zeroing problem for MIMO LTI systems - Tokarzewski, Jerzy (Zielona Góra: Uniwersytet Zielonogórski)
The problem of zeroing the output in an arbitrary linear continuous-time system S(A,B,C,D) with a nonvanishing transfer function is discussed and necessary conditions for output-zeroing inputs are formulated. All possible real-valued inputs and real initial conditions which produce the identically zero system response are characterized. Strictly proper and proper systems are discussed separately.
Keywords: linear multivariable systems; state-space methods; output-zeroing problem; invariant zeros